2003
DOI: 10.1063/1.1623479
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin relaxation due to small-angle motion: Theory for the canonical orientations and application to hierarchic cage dynamics in ionomers

Abstract: Analytical expressions for transverse electron spin relaxation induced by small angle motion were derived for the first time within an anisotropic model for rotational diffusion by using an approximation of the spin Hamiltonian and its variation during reorientation that is valid close to the canonical orientations. The dependence of the decay of the stimulated echo on such motion was studied by extensive Monte Carlo simulations and regimes were identified in which the time constant of this decay is related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 66 publications
(81 reference statements)
0
46
0
Order By: Relevance
“…11,12,21,23 -25 At temperatures above T g , the relaxation is more and more induced by slow (¾10 6 s) molecular orientational diffusion. 8,13,17,26 Nevertheless, ambiguities in the interpretation of ED-EPR data remained for temperatures close to the glass transition where the regimes of slow unrestricted motion and fast restricted motion may overlap. To obtain further insight into the character of the motional process that dominates the transverse relaxation at this temperature, we performed measurements of the transverse relaxation rates at different resonant frequencies ω o (S(3 GHz)-, X(9.5 GHz)-, W(95 GHz)-and G(180 GHz)-bands).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…11,12,21,23 -25 At temperatures above T g , the relaxation is more and more induced by slow (¾10 6 s) molecular orientational diffusion. 8,13,17,26 Nevertheless, ambiguities in the interpretation of ED-EPR data remained for temperatures close to the glass transition where the regimes of slow unrestricted motion and fast restricted motion may overlap. To obtain further insight into the character of the motional process that dominates the transverse relaxation at this temperature, we performed measurements of the transverse relaxation rates at different resonant frequencies ω o (S(3 GHz)-, X(9.5 GHz)-, W(95 GHz)-and G(180 GHz)-bands).…”
Section: Introductionmentioning
confidence: 93%
“…In the expressions, and c are the pulse separation time and the motional correlation time respectively. The parameters A, B and C, which contain the field dependence of the echo-decay functions, are: A D 2 e ∂ H/∂ 2 D/3, with the electron gyromagnetic ratio e , the diffusion coefficient of the orientational motion D and the angular gradient of the Hamiltonian, ∂H/∂ / H 0 ; B D 2 F/ c ) 1 17 By deriving expressions for the echo decays at the canonical g-matrix positions, the authors found monoexponential decay functions with relaxation rates showing a square-root dependence on the external magnetic field (Eqns 13-15, A1-A3 in Ref. 17).…”
Section: -31mentioning
confidence: 99%
“…HF-EPR is widely used in polymer science [10,11,19,[41][42][43][44]. One major feature is the remarkable orientation resolution [44] due to increased magnitude of the anisotropic Zeeman interaction leading to a wider distribution of resonance frequencies [45]. Recently, HF-EPR studies evidenced the exponential distribution of the energy barriers of the deep structure of the energy landscape [19] as well as clear signatures of the onset of fast motion in glassy PS [43,44] in full agreement with neutron [1][2][3][4][5] and Raman scattering [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…B 0 ffi 3T corresponding to Larmor frequencies about 95 GHz (W band), [37,38] or even larger frequencies [19,39,40]. HF-EPR is widely used in polymer science [10,11,19,[41][42][43][44]. One major feature is the remarkable orientation resolution [44] due to increased magnitude of the anisotropic Zeeman interaction leading to a wider distribution of resonance frequencies [45].…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches in EPR were employed: continuous-wave (CW) EPR [1][2][3][4], including high-field CW EPR [5,6], echo-detected (ED) EPR [7][8][9][10][11][12], stimulated echo decay [13,14], field-step electron-electron double resonance (FS ELDOR) [15][16][17][18][19][20], pulsed two-dimensional EPR [21], and some others. EPR allows addressing the important issues of molecular dynamics 638 s.A. Dzuba et al in glasses, such as the mechanism of motion of individual guest molecules, the cooperative nature of motion, temperature dependence of motion, the relation to glass transition, the distribution of correlation times, ~tynamical heterogeneity and others.…”
Section: Introductionmentioning
confidence: 99%